PERAN RUMAH TAHFIDZ TAZKIA YOGYAKARTA SEBAGAI PENUNJANG SPIRITUALITAS SANTRI MELALUI KEGIATAN TAHFIDZUL QUR’AN [THE ROLE OF RUMAH TAHFIDZ TAZKIA YOGYAKARTA AS A SUPPORTER OF THE SPIRITUALITY OF ISLAMIC STUDENTS THROUGH TAHFIDZUL QURAN ACTIVITIES] - Nurfadhilla, Nona; Maturidi, M (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2022)
Rumah Tahfidz Tazkia is one of the places that was built as a foundation that accommodates Islamic students who want to become hafidzah of the Qur'an. Tahfidzul Qur'an is considered to be one way for students to have good spirituality so that they are able to control themselves in all aspects of life. The purpose of this study was to find out how the role of the Rumah Tahfidz Tazkia as a supporter of the spirituality of Islamic students through tahfidzul Qur'an activities. This study uses a qualitative methodology with data collection techniques through interviews and observations. The results of the study indicate that the Rumah Tahfidz Tazkia plays an important role in supporting the spirituality of Islamic students by holding various activities such as tahfidzul Qur'an and various Islamic studies. This is proven by the students who try to become hafidzah, which indirectly also shapes spirituality to be closer to Allah SWT. Islamic students apply the meanings of the Qur'an in their daily lives by amar ma'ruf nahi munkar. So, that Islamic students have high spirituality because they are aware of their closeness to Allah SWT.